2009
DOI: 10.1111/j.1365-3180.2009.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre‐ and post‐emergence weed harrowing on annual weeds in peas and spring cereals

Abstract: Summary To assess the effects of timing and frequency of weed harrowing on weed abundance and crop yield, different pre‐ and post‐emergence weed harrowing sequences were applied to spring cereals and peas in field experiments performed during 2003 and 2004 in Sweden. Post‐emergence harrowing was performed at crop growth stages 2–3 and 5–6 true leaves respectively. The best weed control was obtained by a combination of pre‐ and post‐emergence harrowing, but these treatments also caused yield losses of 12–14% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 21 publications
2
37
1
Order By: Relevance
“…The analysis of variance for the variables related to weed presence and their biodiversity it is not resulted statistically significant, but the average number of weed plants for each crops variety (Table 4) it is in line with other experiments on field bean in Tuscany (Barberi et al, 2004) and pea (Lundkvist, 2009) in organic farming systems and white lupin (Carruthers et al, 2008) in conventional one. The number of weeds seems not to affect the yield of the field pea and field bean, which are in line with the yields expected.…”
Section: Discussionsupporting
confidence: 85%
“…The analysis of variance for the variables related to weed presence and their biodiversity it is not resulted statistically significant, but the average number of weed plants for each crops variety (Table 4) it is in line with other experiments on field bean in Tuscany (Barberi et al, 2004) and pea (Lundkvist, 2009) in organic farming systems and white lupin (Carruthers et al, 2008) in conventional one. The number of weeds seems not to affect the yield of the field pea and field bean, which are in line with the yields expected.…”
Section: Discussionsupporting
confidence: 85%
“…The lack of pre-emergence tillage effect on weed density contradicts the findings of Lundkvist (2009) who reported that pre-emergence harrowing reduced wild mustard density in field pea by 18 to 84% although results in spring wheat and oats (Avena sativa L) were variable. In New Zealand, Dastgheib (2004) reported a 40 to 50% reduction in weed density from preemergence harrowing in field pea.…”
Section: Weed Density and Biomasscontrasting
confidence: 54%
“…Yields of both the pre-emergence tillage treatments at the mid-May seeding date were 81% of the early May DH treatment. The improvement in field pea yield from pre-emergence tillage contradicts studies conducted in Sweden by Lundkvist (2009) who reported that pre-emergence harrowing reduced weed density, but had no effect on field pea yield. In New Zealand, Dastgheib (2004) reported that pre-emergence harrowing improved field pea yields by 54 to 59% compared with untreated controls, which is slightly higher than the mean yield response (33%) reported in this study.…”
Section: Weed Density and Biomassmentioning
confidence: 91%
“…The late emerging annual weed species C. album and Polygonum lapathifolium were most effectively controlled when pre-emergence weed harrowing was combined with one or two weed harrowing treatments after crop emergence. The best weed control was obtained by a combination of pre-and post-emergence harrowing, but these treatments also caused yield losses of 12-14% in spring cereals, while no yield losses were observed in peas (Lundkvist, 2009 Table 3. Total number of weed plants (m -2 ) in the 4 field experiments with peas treated with different combinations of pre-(pre-wh) and post-weed harrowing (post-wh) at Enköping (En) and at Uppsala (Ua) in (Lundkvist, 2009.…”
Section: Weed Harrowingmentioning
confidence: 99%
“…Post-emergence harrowing (postwh) occurs after the crop has emerged and is challenging because both weeds and crop may be damaged by the harrow (Rasmussen et al, 2008) and the most sensitive development stage for mechanical disturbance often coincides for both the crop and the weeds. Given the increasing need for harrowing as a means of weed control and the lack of information on the effectiveness of the many combinations of pre-wh and post-wh treatments that are possible, particularly with respect to field sites in far northern Europe, a project was initiated to study the effects of different combinations of weed harrowing before and after crop emergence on weed control in field sites in Sweden (Lundkvist, 2009). The major hypotheses were (i) that combinations comprising both pre-wh and post-wh provide better weed control effect against annual weed infestations than treatments containing only pre-emergence harrowing, and (ii) that pre-emergence harrowing alone or in combination with post-emergence harrowing provides better control of early emerging weed species versus post-emergence harrowing alone.…”
Section: Weed Harrowingmentioning
confidence: 99%